Peran Ayah dalam Program Pengasuhan Anak Usia Dini Selama Pandemi Covid-19 dari Dimensi Paternal Involvement - Puji Dwi Rahayu (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
The role of fathers in raising children is an important factor that supports the success of the child's learning process during a pandemic. The reality shows that fathers only have a little time to fulfil their role in raising children. This study aims to determine the role of fathers in raising children from the dimension of paternal involvement during Covid-19. This research belongs to the descriptive quantitative research with a survey approach. The subjects involved in this study were 256 fathers who had early childhood. Data collection in this study was carried out using a closed questionnaire method. The data obtained in the study were then analyzed using descriptive statistics. The results of the research analysis show that the role of fathers in childcare during the Covid-19 pandemic from the dimension of paternal involvement is evidenced by fathers as playmates, fathers giving affection, fathers having time and interaction together and communication, fathers giving examples of play, fathers watching children play with friends, dad makes decisions on activities, dad plans to go together, dad invites worship together. Based on these results, it can be concluded that the role of fathers in childcare programs during Covid-19 is in the always and often category.